Relationship between fibrillin-1 genotype and severity of cardiovascular involvement in Marfan syndrome. Issue 22 (3rd May 2017) - Franken, Romy; Teixido-Tura, Gisela; Brion, Maria; Forteza, Alberto; Rodriguez-Palomares, Jose; Gutierrez, Laura; Garcia Dorado, David; Pals, Gerard; Mulder, Barbara JM; Evangelista, Artur
Abstract : Background: The effect of FBN1 mutation type on the severity of cardiovascular manifestations in patients with Marfan syndrome (MFS) has been reported with disparity results. Objectives: This study aims to determine the impact of the FBN1 mutation type on aortic diameters, aortic dilation rates and on cardiovascular events (ie, aortic dissection and cardiovascular mortality). Methods: MFS patients with a pathogenic FBN1 mutation followed at two specialised units were included. FBN1 mutations were classified as being dominant negative (DN; incorporation of non-mutated and mutated fibrillin-1 in the extracellular matrix) or having haploinsufficiency (HI; only incorporation of non-mutated fibrillin-1, thus a decreased amount of fibrillin-1 protein). Aortic diameters and the aortic dilation rate at the level of the aortic root, ascending aorta, arch, descending thoracic aorta and abdominal aorta by echocardiography and clinical endpoints comprising dissection and death were compared between HI and DN patients. Results: Two hundred and ninety patients with MFS were included: 113 (39%) with an HI- FBN1 mutation and 177 (61%) with a DN- FBN1 . At baseline, patients with HI- FBN1 had a larger aortic root diameter than patients with DN- FBN1 (HI: 39.3±7.2 mm vs DN: 37.3±6.8 mm, p=0.022), with no differences in age or body surface area. After a mean follow-up of 4.9±2.0 years, aortic root and ascending dilation rates were increased in patients with HI- FBN1 (HI: 0.57±0.8 vs DN: 0.28±0.5 mm/year, p=0.004 and HI: 0.59±0.9 vs DN: 0.30±0.7 mm/year, p=0.032, respectively). Furthermore, patients with HI- FBN1 tended to be at increased risk for the combined endpoint of dissection and death compared with patients with DN- FBN1 (HR: 3.3, 95% CI 1.0 to 11.4, p=0.060). Conclusions: Patients with an HI mutation had a more severely affected aortic phenotype, with larger aortic root diameters and a more rapid dilation rate, and tended to have an increased risk of death and dissections compared with patients with a DN mutation.